Edukasi Zat Aditif Makanan dan Jajanan Sehat Pada Pelajar - Muzakir, Haris; Ashari, Chica Riska; Listiowaty, Endang (Universitas Negeri Gorontalo, 2023)
The food sold in the market contains many unhealthy additives, such as preservatives, artificial colourings, and sweeteners. Consuming healthy snacks can provide numerous health benefits to students. Healthy snacks made from natural ingredients without harmful additives can provide adequate nutritional intake, improve energy levels, and enhance concentration during the study. The educational goal was to enhance the understanding of food additives and healthy snacks among the students of SMK 2 Muhammadiyah Jakarta. The implementation method of community engagement includes identifying issues related to unhealthy food, conducting a pre-test to assess initial knowledge, providing education and training to students, conducting a post-test to measure knowledge improvement, and evaluating and analysing data to enhance future programs. The pre-test was conducted before the activities to measure the knowledge, behaviour, or skills of the students regarding healthy food and food additives. The post-test was conducted after the completion of activities to measure the increase in students' knowledge, behaviour, or skills after receiving education and training. Community engagement activities in SMK 2 Muhammadiyah can enhance student awareness of the importance of choosing healthy snacks and avoiding harmful additives.